2013
DOI: 10.1016/j.neurobiolaging.2012.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Age-related GABAA receptor changes in rat auditory cortex

Abstract: Auditory cortex (AI) shows age-related decreases in pre-synaptic markers for GABA and degraded AI neuronal response properties. Prior studies find age-related increases in spontaneous and driven activity, decreased spectral and directional sensitivity, and impaired novelty detection. The present study examined expression of GABAA receptor (GABAAR) subunit message, protein and quantitative GABAAR binding in young, middle-aged, and aged rat AI, with comparisons to adjoining parietal cortex. Significant loss of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 98 publications
3
50
0
Order By: Relevance
“…In addition, the decreased expression of GABA receptor subunits or GAD had been reported in the other cortex of rodent or primate in aged groups (Gutierrez et al, 1994(Gutierrez et al, , 1997Caspary et al, 1999;Ling et al, 2005;Rissman et al, 2006;Caspary et al, 2013). These data suggested a reduction in GABAergic inhibition in senescence ones, which might be one of the key mechanisms explaining the decline of visual function during senescence.…”
Section: Introductionmentioning
confidence: 53%
“…In addition, the decreased expression of GABA receptor subunits or GAD had been reported in the other cortex of rodent or primate in aged groups (Gutierrez et al, 1994(Gutierrez et al, , 1997Caspary et al, 1999;Ling et al, 2005;Rissman et al, 2006;Caspary et al, 2013). These data suggested a reduction in GABAergic inhibition in senescence ones, which might be one of the key mechanisms explaining the decline of visual function during senescence.…”
Section: Introductionmentioning
confidence: 53%
“…Declines in the function of inhibitory circuits in the auditory cortex, which is mostly mediated by GABAergic interneurons through feed-forward or feedback connections, have been documented in detail in aging animal models (4,23,24,(51)(52)(53). These major types of GABAergic interneurons expressing PV and SOM are argued to contribute to cortical signal representation, local and system coordination, and experience-dependent plasticity (14,18,22,(54)(55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…Previous animal studies have demonstrated changes in GABAergic neurotransmission in the inferior colliculus (Caspary et al, 1999; Caspary et al, 1990; Ouda and Syka, 2012), cochlear nuclei (Tang et al, 2014) and auditory cortex (Caspary et al, 2013; Ling et al, 2005; Ouda et al, 2008) of the Fischer 344 rat (a model of presbycusis), including decreased concentrations of GABA, decreased GABA release, decreased GABA B receptor binding and decreased numbers of presynaptic terminals. Therefore, reduced GABA+ concentrations in patients with presbycusis might reflect dysfunctional GABAergic neurotransmission in the central auditory system.…”
Section: Discussionmentioning
confidence: 99%